InAs0.91Sb0.09 photoconductor for near and middle infrared photodetection. (29th September 2016) - Tong, Jinchao; Xie, Yiyang; Ni, Peinan; Xu, Zhengji; Qiu, Shupeng; Tobing, Landobasa Y M; Zhang, Dao-Hua
Abstract: Antimonide based III–V materials have been attracting great attention as they have wide applications covering photodetection, light source, photovoltaics and electronic devices. In this paper, we report on the structural and optical properties and photodetection performance of an InAsSb layer grown on a GaSb substrate by molecular beam epitaxy (MBE). An x-Ray diffraction (XRD) study shows that the Lattice-mismatch between the GaSb substrate and the InAsSb epitaxial layer is about 0.17% and the derived composition of Sb is about 0.09. Photoluminescence measurements at varied temperatures reveal that the energy band gap of the InAsSb material is about 0.33 eV and the luminescence peaks follow Bose–Einstein relation. The photoconductors fabricated based on the InAsSb/GaSb structure show spectral response ranging from NIR to MWIR range. They can work well at low voltage bias and the measured blackbody detectivitives are ∼2.4 × 10 7 cmHz 1/2 W −1 and ∼6.1 × 10 9 cmHz 1/2 W −1 at room temperature and 77 K, respectively.